The way out : how to overcome toxic polarization - Coleman, Peter T., 1959- (New York : Columbia University Press, 2021)
"The partisan divide in the United States has widened to a chasm. Legislators vote along party lines and rarely cross the aisle. Political polarization is personal too-and it is making us miserable. Surveys show that Americans have become more fearful and hateful of supporters of the opposing political party and imagine that they hold much more extreme views than they actually do. We have cordoned ourselves off: we prefer to date and marry those with similar opinions and are less willing to spend time with people on the other side. How can we loosen the grip of this toxic polarization and start working on our most pressing problems? The Way Out offers an escape from this morass. The social psychologist Peter T. Coleman explores how conflict resolution and complexity science provide guidance for dealing with seemingly intractable political differences. Deploying the concept of attractors in dynamical systems, he explains why we are stuck in this rut as well as the unexpected ways that deeply rooted oppositions can and do change. Coleman meticulously details principles and practices for navigating and healing the difficult divides in our homes, workplaces, and communities, blending compelling personal accounts from his years of working on entrenched conflicts with lessons from leading-edge research. The Way Out is a vital and timely guide to breaking free from the cycle of mutual contempt in order to better our lives, relationships, and country"--
Introduction: Our Crisis and Opportunity -- Why We Are Stuck -- Attracted to Conflict -- Think Different-Change Your Theory of Change -- Reset-Capture the Power of New Beginnings -- Bolster and Break-Locate Latent Bubbles -- Complicate-Embrace Contradictory Complexity -- Move-Activate Novel Pathways and Rhythms -- Adapt-Seek Evolution for Revolution -- Conclusion: New Rules for The Way Out.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on June 10, 2021)
JSTOR
Keywords: Conflict management -- United States; Polarization (Social sciences) -- United States; Political participation -- United States; Interpersonal relations -- United States; Gestion des conflits -- États-Unis.; Polarisation collective -- États-Unis.; Participation politique -- États-Unis.; PSYCHOLOGY / Social Psychology; Conflict management; Interpersonal relations; Polarization (Social sciences); Political participation; United States